A General Inequality for CR-Warped Products in Generalized Sasakian Space Form and Its Applications. (10th August 2021) - Li, Yanlin; Ali, Akram; Ali, Rifaqat
Abstract : In the present paper, by considering the Gauss equation in place of the Codazzi equation, we derive new optimal inequality for the second fundamental form of CR-warped product submanifolds into a generalized Sasakian space form. Moreover, the inequality generalizes some inequalities for various ambient space forms.